Permanent Income, Liquidity, and Expenditure on Automobiles: Evidence From Panel Data - Bernanke, Ben S. (Quarterly Journal of Economics, 1984)
Several recent papers have tested the permanent income-cum-rational expectations hypothesis using data on nondurable or semidurable consumption. We show how this approach can be extended to the case of durables. An application to panel data on automobile expenditures reveals no evidence against the permanent income hypothesis. This result is unchanged in subsamples segregated by family holdings of liquid assets.